Birds at risk in warming southern African deserts: inferences from behavioural and physiological thermoregulation - Louw, Gina (Percy FitzPatrick Institute of African Ornithology, 2015)
The study focused on avian species' responses to high ambient temperature. Ambient temperature is a variable to which birds are particularly sensitive and which climate-change models predict will increase disproportionately rapidly in southern Africa's hot deserts, especially the Kalahari.